Fracture of upper incisors: a three-year follow-up of a multidisciplinary approach - CALDAS,Ricardo Armini (2021)
ABSTRACT Multiple clinical specialties are usually needed for a successful long-term treatment in buccal cavity. The aim of this article is to report a clinical case of multi-disciplinary rehabilitation of fracture upper incisors without pulp exposure, concerning about endodontics, periodontics and restorative dentistry comments or procedures. A case of a patient reporting trauma that resulted in fracture and substantial loss of hard tissue, in mesial angle of both upper central incisors (11 and 21). In palatal side, fracture extended beyond cingulum up to subgingival region. Periodontal surgery was performed in order to reestablish biological space. Clinical and radiographic assessments demonstrated no need for endodontic treatment, since pulp was vital and non-altered. Preparations for restorative procedures were minimally invasive, followed by composite direct. A three-year follow-up was performed, consisting in re-assessment of clinical and radiographic aspects, re-polishing of the restorations and photographic documentation. No pulp tissue alteration was observed after the follow-up period. Restorative procedures, adjacent tissues and pulp vitality were considered adequate, and the patient was satisfied with the treatment.